Earning Per Share dan Return On Assets sebagai prediktor Harga Saham perusahaan Transportasi di Indonesia - Isthi Wahyu Ningtyas; Dede Yulita Sari (International Journal of Digital Entrepreneurship and Business, 2023)
This study investigates the relationship between earnings per share, return on assets, and stock prices. This research uses a quantitative methodology, and we use financial reports and annual reports from the Indonesian Stock Exchange (IDX) as secondary data sources. Infrastructure development will have an impact on economic growth both directly and indirectly. Transportation is one of the infrastructures that is essential in supporting humans to carry out their activities. Transportation is a means that plays a vital role in supporting economic growth and regional growth, so it is often referred to as the lifeblood of the economy. So in this research, we use the transportation industry as our sample. We use purposive sampling to select the samples. Twenty transportation companies comprise the selection in this research from the population of companies on the Indonesia Stock Exchange from 2017 until 2021, so the research period is five years long. According to the findings, Earning Per Share significantly and positively influences stock price. The stock price also has significantly and positively impacted by Return on Assets. The results showed a simultaneous impact of Earning Per Share and Return on Assets on stock prices. So, the factors that influence the company’s stock price is Earning Per Share and Return on Assets.